INTEGRASI GUGUSAN SUBSTANSI MANAJEMEN PENDIDIKAN ISLAM DALAM MENINGKATKAN MUTU LEMBAGA: ANALISIS LIMA KOMPONEN MANAJEMEN PENDIDIKAN - Mukhammad Ishomuddin; Eko Wahyudi; Muhammad Sholahuddin Arif (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the concept of the Islamic educational management substance cluster as an integrated management model in improving the quality of Islamic educational institutions in the era of globalization and the industrial revolution 4.0. The study uses a descriptive qualitative approach with a library research method through data collection from various literature sources in the form of books, journal articles, theses, and dissertations relevant to the study of Islamic educational management. The data is analyzed systematically to find conceptual relationships between the substances of Islamic educational management. The results show that the Islamic educational management substance cluster consists of five main components, namely curriculum management, human resources, student affairs, infrastructure, and public relations which are integrated into a holistic and dynamic management system. The integration of these five components can create strategic synergy in improving the effectiveness of institutional governance, the quality of learning, the professionalism of educators, strengthening student character, optimizing educational facilities, and strengthening the institution's image in the community. This study also found that the Islamic vision and mission serve as a central orientation in connecting all management substances so as to create a balance between Islamic values ​​and modern management practices.